How Resilient Was Trade to Covid-19? - Maria Bas; Ana Margarida Fernandes; Caroline Paunov (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine the supply-side characteristics - unskilled labor, imported input intensity, dependence on inputs from China, production complexity - that determine different potential vulnerabilities of traded products to the COVID-19 pandemic. Relying on monthly exports at the product level by all countries to the United States, Japan, and all 27 European Union countries from January 2018 to December 2020, we estimate a difference-in-differences specification of the COVID-19 incidence (deaths per capita) mediated by product vulnerabilities. We account for the precise lag between when the COVID-19 shock hit the exporting country and when exports reach their destination country relying on the products' type of transportation and distance between exporter and importer countries. Higher reliance on foreign inputs, on China as input supplier, on unskilled labor and a lower degree of complexity negatively affected exports as a result of this shock.
Keywords: F14; F61; D20; 330; exports; vulnerability; resilience; Covid-19; shock; high-frequency data